2021
DOI: 10.1186/s12934-021-01563-w
|View full text |Cite
|
Sign up to set email alerts
|

Oral probiotic activities and biosafety of Lactobacillus gasseri HHuMIN D

Abstract: Background Lactobacillus spp. have been researched worldwide and are used in probiotics, but due to difficulties with laboratory cultivation of and experimentation on oral microorganisms, there are few reports of Lactobacillus spp. being isolated from the oral cavity and tested against oral pathogens. This research sought to isolate and determine the safety and inhibitory capabilities of a Lactobacillus culture taken from the human body. Results On… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 93 publications
1
23
0
Order By: Relevance
“…28 L. fermentum and L. gasseri can release anti-microbial agents such as bacteriocins, 29,30 biosurfactant 31,32 and hydrogen peroxide. 33,34 In line with this, our results showed that LF23 and LG80 fermentation supernatants could significantly inhibit the growth of H. pylori and reduce H. pylori infection in vivo , indicating that they can metabolize and produce bacteriostatic substances. In the case of excluding the influence of acid, the fermentation supernatant of LAB can also significantly inhibit the growth of H. pylori , indicating that in addition to the secretion of organic acids, it can also produce other antibacterial substances.…”
Section: Discussionsupporting
confidence: 82%
“…28 L. fermentum and L. gasseri can release anti-microbial agents such as bacteriocins, 29,30 biosurfactant 31,32 and hydrogen peroxide. 33,34 In line with this, our results showed that LF23 and LG80 fermentation supernatants could significantly inhibit the growth of H. pylori and reduce H. pylori infection in vivo , indicating that they can metabolize and produce bacteriostatic substances. In the case of excluding the influence of acid, the fermentation supernatant of LAB can also significantly inhibit the growth of H. pylori , indicating that in addition to the secretion of organic acids, it can also produce other antibacterial substances.…”
Section: Discussionsupporting
confidence: 82%
“…Several strains of L. paracasei have also been reported to inhibit S. mutans biofilm formation [52,53]. Mann et al [54] reported that L. gasseri inhibited the formation of biofilm by S. mutans on an orthodontic wire. Moreover, it has been reported that S. salivarius can respond to plaque formation and salivary acidity by producing dextranase and urease after colonizing the oral mucosa of humans [28].…”
Section: Discussionmentioning
confidence: 99%
“…Intake of fermentative food, fruits, and vegetables by a 10-month-old baby may be the reason for the existence of L. mesenteroides in the oral cavity. L. gasseri is a widely studied probiotic species with various biological functions, including oral probiotic characteristics ( 30 ). L. gasseri is known as a part of the vaginal flora, and some researchers isolated L. gasseri from breast milk ( 31 ) or saliva ( 27 ).…”
Section: Discussionmentioning
confidence: 99%